(الوقف والابتداء في القرآن الكريم والاستفادة منهما في تعليم اللغة العربية (سورة الملك نموذجا - RUSLAN (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
Arabic is the noblest language absolutely, because al-quran is revealed in arabic, and with it a muslim can understand the islamic shari’a which was delivered by the messenger of allah, and the knowledge of Al-waqf and Al-ibtida’ is part of the branch of Arabic sciences that can help the readers of qur’an, the instructors as well as the learners in understanding the meaning of Al-quran correctly. It also helpful to avoid mistakes that can change the meaning of the verse. Therefore this research aims to explain the meaning of Al-waqf and Al-ibtida’ and to identify the kinds in surat Al-mulk and analyze them in detail and implement them in teaching arabic. In the study of this topic researcher used a descriptive analytical approach system, namely by collecting and searching for information related to the topic to achieve the results, and then analyzing these results and applying them in the field of teaching arabic. This research shows that Al-waqf and Al-ibtida’ is a science that discusses the procedure for reading the Al-qur’an to avoid a false understanding of the meaning of the verse of the Al-quran and to safeguard the authenticity of the Holy Qur’an, and Al-ibtida’ is a science that discusses the procedure for starting in reading the Al-qur’an in order to perfect its meaning, and this study shows that Al-waqf and Al-ibtida’ in surat Al-mulk are divided in to four types namely At-taam, Al-hasan, Al-kaafi and Al-qobih, and indeed Al-waqf and Al-ibtida’ play and important role in maintaining the purity of the Qur’an, and shows that the science of Al-waqf and Al-ibtida’ is closely related to the science of annahwu and interpretation, and its urgency in teaching Arabic.